2014
DOI: 10.3390/nu6104552
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Food Addiction as Assessed by the Yale Food Addiction Scale: A Systematic Review

Abstract: Obesity is a global issue and it has been suggested that an addiction to certain foods could be a factor contributing to overeating and subsequent obesity. Only one tool, the Yale Food Addiction Scale (YFAS) has been developed to specifically assess food addiction. This review aimed to determine the prevalence of food addiction diagnosis and symptom scores, as assessed by the YFAS. Published studies to July 2014 were included if they reported the YFAS diagnosis or symptom score and were published in the Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

65
423
16
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(515 citation statements)
references
References 65 publications
(426 reference statements)
65
423
16
11
Order By: Relevance
“…The meta-analysis revealed that, according to the YFAS, the mean prevalence of the diagnosis of "food addiction" was almost 20%, being higher in patients suffering from BN than in cases of BED. In accordance with most of the aforementioned studies, "food addiction" was associated with higher tendency to binge eating, depressive symptoms, impulsivity, and emotional eating [48].…”
Section: Does Food Addiction Exist?supporting
confidence: 86%
“…The meta-analysis revealed that, according to the YFAS, the mean prevalence of the diagnosis of "food addiction" was almost 20%, being higher in patients suffering from BN than in cases of BED. In accordance with most of the aforementioned studies, "food addiction" was associated with higher tendency to binge eating, depressive symptoms, impulsivity, and emotional eating [48].…”
Section: Does Food Addiction Exist?supporting
confidence: 86%
“…Recently, a revised version based on the DSM, version 5 (DSM-5), substance-related and addictive disorders (SRAD) criteria was developed and validated (YFAS 2.0) [25]. Generally, approximately 5-10% of individuals in community-based samples exhibit indicators of YFAS ‘food addiction' [24,25], though prevalence is higher among individuals with obesity [26] and binge eating disorder [27,28]. The YFAS has been translated into multiple languages to assess the prevalence of addictive-like eating behavior worldwide [23,26,29].…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong relationship between low DT and substance addiction, it is also quite possible that low DT is associated with food addiction (FA), which does not have a universal definition, but has been described as ''an abnormal pattern of excessive consumption'' [23]. FA is a controversial topic since its very existence is under debate [24].…”
Section: Introductionmentioning
confidence: 99%